Collaboration between developing and developed countries and between developing countries in occupational health research and surveillance - Partanen, TJ; Hogstedt, Christer; Ahasan, R; Aragón, A; Arroyave, ME; Jeyaratnam, J; Kurppa, Kari; Loewenson, R; Lundberg, Ingvar; Ngowi, AVF; Mbakaya, CFL; Stayner, Leslie; et al. (Scandinavian Journal of Work, Environment & Health, 1999)
Collaborative occupational health and safety studies between counterparts in developing and developed countries and between developing countries have demonstrated their potential for improving occupational health and safety. Such collaboration in occupational health and safety is encouraged in the development of infrastructure in research empowerment and capacity building. This action includes the setting of priorities, the identification and documentation of problems, sponsorship, data bases and surveillance systems, technical support, methodology, publishing, research and training programs, controlled intervention, information exchange, and networking. Examples of priorities in occupational health and safety in the developing world include the informal sector (informally hired and independent workers), temporary work, pesticides, accidents, dusts, carcinogens, solvents, ergonomics, women and child labor, human immunodeficiency virus/acquired immunodeficiencey syndrome (HIV/AIDS), and transfer of hazardous materials and technologies. The sustainability of occupational health and safety structures and functions in the developing countries is a primary concern. Socioethical principles emphasize local, national, mutual and global gains. Examples of collaboration are given. Pervasive problems and strategies toward their solution are highlighted.
Keywords: collaboration; cooperation; developed country; developing country; empowerment; impact; infrastructure; occupational health; occupational health research; occupational health surveillance; occupational safety; occupational safety and health; priority; sponsorship; sustainability; training; tropics